Drinking behavior patterns may be associated with persistent depressive symptoms after alcohol abstinence in alcohol use disorder - Kazuhiro Kurihara; Hotaka Shinzato; Yoshikazu Takaesu; Tsuyoshi Kondo (Wiley, 2024)
Abstract Aim This study examined the association between drinking behavior patterns and depressive symptoms after alcohol abstinence in patients with alcohol use disorder (AUD). Method We recruited 102 AUD inpatients with baseline depressive symptoms, indicated by scores ≥6 on the Quick Inventory of Depressive Symptomatology Self‐Report Japanese Version (QIDS‐SR‐J) pre‐detoxification. Post‐4‐week abstinence, remission was defined as QIDS‐SR‐J scores <6. Patients were classified into remitted (n = 51) and persistent (n = 51) groups. Comparative analyses were conducted using patient profiles and the Drinking Behavior Pattern 20‐item Questionnaire (DBP‐20). Logistic regression identified factors related to post‐abstinence persistent depression. Receiver operating characteristic curve analysis determined DBP‐20 cutoff scores differentiating between persistent and remitted depression. Results The persistent group exhibited higher scores in the DBP‐20 "coping with negative affect" subscale. Logistic regression showed low education, unemployment, and using alcohol for coping as significant factors for persistent depression. Conversely, an automatic drinking pattern indicated natural remission post‐abstinence. A subscale score of ≥8 in alcohol use for coping, especially among unemployed patients, predicted persistent depression (sensitivity 86.8%, positive predictive value 73.3%). Conclusion Unemployed patients with AUD using alcohol to cope with negative affect may experience residual depression even after detoxification. In contrast, patients with AUD with predominantly automatic drinking behavior may exhibit natural remission post‐abstinence.